098 Guillain Barré syndrome (GBS) – like presentation as a first clinical manifestation of non-Hodgkin's lymphoma. Issue 6 (27th May 2022) - Siddiqui, Sarah; Poole, Olivia; Midgley, Laura; Vijayan, Ashwathy; Bland, Jeremy; Harikrishnan, Sreedharan; Alkufri, Fadi; Redmond, Ian; Moran, Nicholas
Abstract : A variety of peripheral nerve disorders can be seen in association with lymphomas. We present a case of a 68-year-old female who presented with ten days history of rapid onset ascending paresthesias followed by unsteadiness. Neurological examination was remarkable for truncal ataxia with wide-based gait, large fiber sensory impairment (proprioception/vibration). There was some evidence of autonomic instability given labile blood pressure and tachycardia. MRI head and spine were unremarkable, as was the CSF. She was initially treated as acute ataxic variant of GBS with IVIG; however, there was continued clinical deterioration. Electrophysiology three weeks after symptom onset showed minimally delayed F waves, with normal sensory and motor NCS. Nerve Ultrasound revealed pronounced enlargement of C6 nerve root which was confirmed later with MRI of brachial plexus showing thickening and some enhancement of roots and trunks. Subsequent CT CAP and PET scan showed mediastinal, hilar and supraclavicular lymphadenopathy, though no PET uptake in the region of dorsal root ganglion. Biopsy of the right supra- clavicular node was consistent with an anaplastic large cell lymphoma. Atypical presentations of acute neuropathy can be attributed to GBS; however, they should include evalu- ation of a paraneoplastic process which can have similar acute presentations. This case also demonstrates the importance of nerve ultrasound which can be significantly abnormal in sensory neuronopathy with relatively normal electrophysiological testing. s_hasan_s@yahoo.com